The airborne dilemma - Stephen Z Fadem (Archives of Clinical Nephrology - Peertechz Publications, 2021)
In December 2019, there were 44 cases of an atypical pneumonia found to be related to a novel coronavirus, SARS-CoV-2. The disease was classified as a global health emergency one month later and reached pandemic proportion by March 11, 2020. By October 2020, it had killed over 1,000,000 people. By April 2021, there were nearly 3 million deaths. Not only has this virus been costly in terms of life but has had lasting side effects. It has been difficult to contain, sometimes resulting in overloading of hospital critical care services and disruption of regular care. It has also devastated the economy, particularly sectors related to tourism and transportation. Even the Summer Olympics were postponed. We have had severe pandemics throughout our history, but the last one this devastating was the Spanish Influenza of 1918. The world was unprepared for this onslaught.